Restoration and evaluation for severed streams in high-density urban areas based on a multi-objective framework: A case study of Heping Stream in Nanjing - Fang Yuhao; Hou Qinghe; Cheng Yuning; Cao Yilun; Zhang Xiaohan; Wang Yong (Ecological Indicators)
Numerous severed streams that emerge during rapid urbanization has been negatively impacting regional water systems and urban environments. Traditional restoration efforts are prone to focus on water quality, overlooking the complex of urban severed stream as natural-social ecosystems. However, current literature indicates a lack of systematic restoration methods and post-implementation evaluations tailored to severed streams, which adversely affects water resource management and sustainable urban development. This study bases on research of the severed streams in Nanjing’s Hexi New District to develop methods for the restoration and evaluation of severed streams in high-density urban areas. Taking the Heping Stream as a case study, it took three years to complete a full-process study encompassing the design, implementation, and post-occupancy evaluation of the restoration of the severed stream. We developed a multi-objective framework, including five measures for the restoration of severed streams, along with performance evaluation indicators from environmental, social, and economic perspectives to compare the state of the severed-stream before and after the restoration. So as to assess the effectiveness of the restoration methods and to put forward suggestions for the improvement of the restoration measures. The results showed that the method had a positive effect on the quality of the water environment, public evaluation, capital investment and energy consumption. Some of the environmental performance indicators were significantly improved after the restoration, especially the dissolved oxygen content, water flow. Most of the social performance indicators were better after the restoration than before. In terms of economic performance indicators, the use of photovoltaic energy resulted in significant savings in electricity and pumping costs. Performance evaluation confirmed comprehensive benefits of the method, with Run off Control, Waterfalls Construction and Riverbank Ecological Restoration being most effective. To improve the benefits of restoration, diverse strategies should be combined together, including runoff control, artificial wetlands, vegetated buffers, and riverbank restoration. This research can support the optimization of future restoration measures and scientific decision-making in urban severed-stream restoration.